2000
DOI: 10.1007/s004360000262
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic markers of heart lesion in mice infected with Trypanosoma cruzi and submitted to benznidazole chemotherapy

Abstract: Creatine kinase (CK total and CK-MB) were studied as markers of lesion progression induced by Trypanosoma cruzi infection. After 3 weeks mice infected with 10(4) parasites showed an increase in both enzyme levels and in their frequency distribution. A trend to increase was already detected in the 2nd week. A short duration per os treatment with benznidazole (Bz) prevented the occurrence of tissue lesions, since no changes were observed in enzymes. However, in the 4th week, about 40% of Bz-treated mice showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
1
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 11 publications
7
33
1
4
Order By: Relevance
“…Lastly, we found that during T. cruzi infection, anti-TNF-α treatment partially hampered the development of cardiomyocyte lesions, characterized by the release of CK-MB (de Souza et al 2000), reinforcing the role of TNF-α as a contributor to cardiac injury. Recently, TNF-α blockade has been shown to decrease necrotic areas in the spleen during acute T. cruzi infection (Andrade et al 2008).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Lastly, we found that during T. cruzi infection, anti-TNF-α treatment partially hampered the development of cardiomyocyte lesions, characterized by the release of CK-MB (de Souza et al 2000), reinforcing the role of TNF-α as a contributor to cardiac injury. Recently, TNF-α blockade has been shown to decrease necrotic areas in the spleen during acute T. cruzi infection (Andrade et al 2008).…”
Section: Discussionsupporting
confidence: 57%
“…6a, b). More importantly, inspection of CK-MB levels, one of the markers of myocardial injury (de Souza et al 2000), revealed that anti-TNF-α-treated mice had lower CK-MB levels compared to non-treated or saline-injected T. cruzi-infected C3H/ HeJ mice (Fig. 6d).…”
Section: Tnf/ Tnfr1 Signaling Is Involved In Cardiac Tissue Damage Dumentioning
confidence: 96%
“…cruzi RA strain is known to produce limited cardiac parasitism in chronic murine infection [39], we analyzed more sensitive and broader markers of muscle damage, by measuring the serum levels of the myopathy-associated enzymes CK, LDH and AST. Our rationale for choosing these enzymes was their abundant distribution in heart and muscles, and their increased serum activity in chronically infected hosts showing inflammatory damage [40]. We found significantly reduced enzyme activity in mice vaccinated using distinct immunizing strategies respect to non-vaccinated and infected animals.…”
Section: Discussionmentioning
confidence: 87%
“…The drug solution was sonicated for 15 min and stored at 4°C in the dark. The daily volume consumed by the animals was monitored for calculation of the amount of drug ingested, which corresponded to 62.5 mg of benznidazole/kg/day, as described previously (37).…”
Section: Methodsmentioning
confidence: 99%